NAZMU'L-ULÛM - (:unkn) unknown (My University, 2013)
Nazmu'ladlı mesnevîde, çeşitli ilimler hakkında bilgi verildikten sonra bu ilimlerin öğrenilmesi gerektiği vurgulanmıştır. Mesnevî, arûz vezninin olup 1098/1687 yılında Tokat'ta telif edilmiştir. Mesnevî toplam 422 beyittir. Araştırmalarımız neticesinde yirmi iki nüshasını tespit ettiğimiz mesnevîde çeşitli ilimler hakkında bilgi verililmiştir. Nazmu'lyönüyle manzûm bir nasihatnâme olup öğrenilmesinin öğütlendiği ilimlerin bazıları şunlardır: 1. İlm-i Tecvîd, 2. İlm-i Kelâm, 3. İlm-i Fıkıh, 4. İlm-i Tasavvuf ve Ahlâk, 5. İlm-i Hadîs, 6. İlm-i Tefsîr, 7. İlm-i Tıp, 8. İlm-i Lugat, 9. İlm-i Nahv ve Sarf, 10. İlm-i Mantık, 11. İlm-i Edeb, 12. İlm-i Usûl-i Fıkıh, 13. İlm-i Meânî, 14. İlm-i Hesâb, 15. İlm-i Hendese, 17. İlm-i Kîmyâ, 18. İlm-i Arûz, 19. İlm-i Eş'âr. Mesnevîde kullanılan kelimler incelendiğinde Arapça ve Farsça kelimelerin çokluğu dikkat çekmektedir. Bu kelimelerin çokluğunun nedenini, devrin şartlarında, müellifin Arapça ve Farsçaya hâkimiyetinde ve mesnevînin dinî bir karatter göstermesinde aramak gerekir. Ama eserin bu özelliği onun akıcılığından bir şey kaybettirmemiştir. Mesnevîde, bolca söz sanatlarına ve tasvirlere yer verilmiş, gereksiz ifadelerden kaçınılmaya çalışılmıştır. Mesnevînin müellifi İshâk Efendi, arûz veznine ve dile hâkim bir şâirdir. Nazmu'ldüşmeden dili rahatlıkla kullanması dikkat çekicidir. Bu özellik İshâk Efendi'nin şâirlik gücüne, çok sayıda şiir yazmasına ve yaşadığı dönem olan on yedinci yüzyıla değin Türkçe anlatımdaki gelişmeye de bağlıdır.

As manuscript works, which constitute some indispensable treasure with respect to history of our literature, come back into light, our knowledge on religious literary genres, as well as other, no doubt increases. Such works added to literature thanks to efforts by researchers give us the opportunity of close acquaintance with religious works that are considered as the most significant and the most prolific products of Divan Poetry, and of more accurate interpretations regarding the genre of such works. Apart from works such as aqâid, fiqh and catechism (ilm-i hal) in verse, siyer (life of Muhammad) in verse, exegeses (tafsir) and hadithes in verse that are generally written in poetic structure for these disciplines, there are also some poetic pieces about a subdivision or important question of abovementioned Islamic sciences. Faraiz, Hegira of Muhammad, miraj-name, rules of hajj, miracles of Prophet, all in verse, can be mentioned among such examples. In the wake of our researches, we found out that these catechisms in verse constitute a notable part of our religious literature. Tokatlı İshâk Efendi was an important poet and writer who lived in 17 th century. Biographic sources dores not mention him alot. The poetry in rhymed couplets, Nazmu'lhow important poet he is. At his Nazmu'linformation about different sciences and wants them to learn. Because of these properties Nazmu'lhave got strong rhymes. That is possible to say poetry in rhymed couplets have fascinating expressions rather than bare tellings. So many telling arts and describtions were given place in that book. , which we are working on shows us İshâk Efendi gives is a written verse advice. Nazmu'l.
Turkish Studies - International Periodical For The Languages, Literature and History of Turkish or Turkic